TEXTUAL VS. SCHEMATIC TEACHING MATERIAL IN A LESSON OF RUSSIAN AS A FOREIGN LANGUAGE IN A CHINESE AUDIENCE - Budnik, Ekaterina; Bankova, Sofia; Shilenko, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The Russian language continues to maintain a leading position as a foreign language in China. Every day students have to work with much information in Russian. According to the confirmed data, the Chinese are representatives of cultures of the right-brain type of thinking. Today some works touch on the psychological and pedagogical aspects and linguo-methodological foundations of teaching Chinese students. The researchers believe it is possible to classify Chinese students as individuals with a significant dominance of the brain's right hemisphere. This is related to the specificity of the cognitive style of their educational activity, which manifests itself in the following features: in an inductive, concrete-nonlinear type of thinking, which allows one to perceive information holistically, at one time, in establishing connections not from word to word, but from image to word, with an important role of a visual image. Leading methodologists and psycholinguists recommend considering the dominance of the right hemisphere to increase the effectiveness and efficiency of teaching Russian as a foreign language to Chinese. Nevertheless, the design of the educational material of the lesson is still formalized in a traditional, textual form. The article aims to experimentally answer the question: in what form, textual or schematic, Chinese students perceive and remember information better. The authors used an experimental method, which consisted in studying the development of educational material depending on the form of presentation: text or schematic. As a result of the experiment, it was revealed that Chinese students make much fewer mistakes when studying the material in a schematic form.